To understand such cases, let's have an example.
Considering this circuit:
Here are the steps in solving:
1. Analyze circuit.
2. Look at the figure. I have assigned I1 for the first current loop and I2 for the second current loop.
3. Since that the second loop has the current source of 2 amperes,therefore,I conclude that:
I2 = -2 Amps
4. Solve Mesh 1 to get I1:
---------------------------------------------------------------------------------
12/_0 + 3I1 - j2(I1-I2) = 0
12/_0 + 3I1 - j2I1 - j2I2 = 0
12/_0 + I1(3-j2) - j2I2 = 0
I1(3-j2)-j2I2 = -12/_0
I1(3-j2)-j2(-2/_0) = -12/_0
I1(3-j2)+j4 = -12/_0
I1 (3-j2) = -12/_0 - j4
I1 = 3.508/_-127.87 Amps
Itotal = 4.99/_-146.30 Amps
---------------------------------------------------------------------------------
V = IR
V = (4.99/_-146.30)(j2)
V = 9.98/_-56.307 Volts
Considering this circuit:
Here are the steps in solving:
1. Analyze the circuit.
2. In this case, the current source is in between of two meshes. Then it will be changed by an open circuit. See the figure below.
3. Solve for Supermesh by using KVL:
-j2I1 - 3I2 = 0 ----------> Equation 1
- Get I2 by KCL:
I2 = 2/_0 + I1 ----------> Equation 2
- Substitute Eq. 2 in 1:
-j2I1 - 3(2/_0 + I1) = 0
-j2I1 - 6 - 3I1 = 0
I1(-3-j2) = 6
I1 = 1.664/_146.309 A
- for I2:
I2 = 2/_0 + 1.664/_146.309
I2 = 1.109/_56.309 Amps
- Solve for V:
V = IR
V = 1.109/_56.309(3)
V = 3.328/_56.309 Volts